Greenhouse Gas Emissions from a Petroleum Naphtha Storage Tank - Pavaris Charuchitsopon; Peemapat Jookjantra; Pornpavit Mapraditkul; Korn Premrungchet; Sirapong Sooktawee; Sarawut Thepanondh (Asian Health, Science and Technology Reports, 2026)
Greenhouse gas (GHG) emissions from a petroleum naphtha storage tank are a significant environmental concern. During crude oil refining, naphtha accounts for approximately 20–30% of total products as a key feedstock for petrochemical industries worldwide. However, naphtha storage is one of the most pressing issues in Thailand due to the use of Fixed Roof Tank (FRT) lacking effective vapor control mechanisms, which leads to fugitive GHG emissions. This study estimated GHG emissions at the petroleum refinery in Chonburi Province from four types of petroleum naphtha storage tanks, including FRT without emission control, FRT with a Vapor Recovery System (FRT-VRS), Internal Floating Roof Tank (IFRT), and External Floating Roof Tank (EFRT), using the TANKS 5.1 model, GHG emissions calculation equations, and Root Cause Analysis (RCA). The results indicate that FRT without emission control emits the highest at 7,476.83 kg/year, while EFRT releases a total of 2,093.51 kg/year. FRT-VRS reduces emissions by 90% to 747.68 kg/year. IFRT has the lowest emissions at 267.49 kg/year. This study highlights the importance of implementing effective control technologies and operational improvements to minimize environmental impacts and promote long-term sustainable industrial management.